Piano sonata no. 6 in F major, op. 10, no. 2, edited by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (Stuttgart; Germany; Eduard Hallberger, 2024)
Mid-nineteenth century edition of the Piano Sonata no.6 in F major, op. 10. no. 2, edited by Ignaz Moscheles and published by Eduard Hallberger in Stuttgart as no. 6 of the series "L. v. Beethoven's sämmtliche Sonaten für Pianoforte."